Molecular and morphological characterization of Chrysomya bezziana (Diptera: Calliphoridae) in Egypt - Salwa S. Rashed; Emad I. M. Khater; Rawda M. Badawy; Abdalla H. Radwan; Eman E. Zaher (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Chrysomya bezziana (Villeneuve, 1914), the screw-worm fly, is a significant parasitic blow fly species that causes obligatory myiasis in livestock and, in some cases, in humans. Its ability to infest wounds and cause extensive tissue damage makes it a significant concern in the veterinary and public health sectors. Accurate and timely identification of C. bezziana is critical for managing outbreaks and implementing control measures. This study confirms the occurrence of C. bezziana in Egypt through both morphological and molecular identification, as only a few studies have reported its presence in Egypt so far. Adult samples of C. bezziana were collected using meat-baited traps situated in the cemeteries of two localities in Egypt (Port Said and El-Sharkia Governorates). DNA was extracted from the specimens for molecular identification using the cytochrome oxidase I (cox1) gene. Results Morphologically, C. bezziana adult flies were identified by a row of hairs on the dorsal surface of the wing's stem vein, blackish anterior spiracles, and the most distinctive characteristic, a white calypter with a whitish-yellow distal end, which differentiates this species from the most closely related species, Chrysomya megacephala. Genetically, it was found that based on a 703 bp fragment of the cox1 gene, C. bezziana was accurately identified, and further phylogenetic analysis confirmed the DNA-based identification of adult specimens of C. bezziana examined. This finding confirms the presence of C. bezziana and expands our knowledge of its distribution in Egypt. Conclusion This study is the first to report the occurrence of C. bezziana in Egypt using an integration of molecular and morphological methods.